1973
DOI: 10.1071/bi9731179
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization by Growth Lambs of a Casein-Saffower Oil Supplement Treated With Formaldehyde

Abstract: A formaldehyde-treated casein-safflower oil supplement was given at levels of 0, 75, and 150 gjday to lambs receiving 600 gjday of a diet of equal parts chopped lucerne hay and crushed oats. The response of the lambs was studied in terms of food intake and liveweight gain, the chemical composition of the body, the incorporation of linoleic acid into body fat, the digestibility of the diets, and the levels of urea, a-amino nitrogen, and glucose in blood plasma.The supplemented lambs appeared to discriminate aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

1975
1975
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 4 publications
1
6
1
Order By: Relevance
“…Crude protein digestibility varied from 18.2 to 81.3% in lambs and from 75.9 to 78.4% in kids. Lipid digestibility was approximately 9O% for both species and all treatments; these results are slightly higher than those reported by Faichney et al (1973) rt93 in lambs but similar to those found by Delort-Laval and Gueneau (1971) …”
contrasting
confidence: 46%
See 1 more Smart Citation
“…Crude protein digestibility varied from 18.2 to 81.3% in lambs and from 75.9 to 78.4% in kids. Lipid digestibility was approximately 9O% for both species and all treatments; these results are slightly higher than those reported by Faichney et al (1973) rt93 in lambs but similar to those found by Delort-Laval and Gueneau (1971) …”
contrasting
confidence: 46%
“…(Faichney et al 1973) and for growing goats (Beede et al 1985). Crude protein digestibility varied from 18.2 to 81.3% in lambs and from 75.9 to 78.4% in kids.…”
mentioning
confidence: 99%
“…Polyunsaturated fatty acid levels in tissues of cattle and sheep were significantly elevated by feeding formaldehyde-treated lipid [29][30][31]. Approximately 18-25% of the linoleic acid consumed in formaldehyde-treated lipid was stored in body tissues of cattle [32], while 50-60% storage was reported for sheep [31,33].…”
Section: Formaldehyde-treated Fatsmentioning
confidence: 99%
“…The supposed relationship between dietary saturated fats and cardiovascular degeneration in man has stimulated an interest in the possibility of increasing the levels of polyunsaturated fatty acids, in particular linoleic acid, in ruminant meat and milk (1)(2)(3)(4)(5). Little is known, however, about the effects of such increased levels of linoleic acid upon the metabolism of ruminant tissues.…”
Section: Introductionmentioning
confidence: 99%